Studi Kelayakan Bisnis Pendirian Bank Pembiayaan Rakyat Syariah (BPRS) di Kalimantan Timur - Dedy Mainata; Angrum Pratiwi (Universitas Alma Ata, 2020)
The economy of East Kalimantan as a whole is growing rapidly, however, this was not accompanied by the development of a Sharia Rural Bank (BPRS). This study aims to determine the feasibility of establishing a BPRS in East Kalimantan in terms of financial, marketing, social, economic, and cultural aspects as well as to find out which municipalities are feasible to establish BPRS. This type of descriptive qualitative research, the sample used in Balikpapan and Samarinda, the data collection techniques used observation and interviews. The results showed that the financial aspects of the BPRS were feasible to establish. NPV and IRR calculations show that the investment in the establishment of the BPRS is feasible. The market aspect looks at the potential of GRDP, population and purchasing power. The marketing aspect sees the potential growth of SMEs, business fields and the number of SMEs. Market segmentation and the target market for BPRS are SMEs engaged in trade and culinary. The economic aspect has an impact on regional income, the ease in providing cheap funds for SMEs, opens up community jobs. The social and cultural impact of the community being educated about banking. Balikpapan and Samarinda have great potential for the establishment of a BPRS. Samarinda is the most feasible to establish a BPRS.